(untitled) (Economics and region, 2023)
The article summarises the more than 10-year history of artificial intelligence in business. Based on the data on investments in the world’s 100 largest AI startups, the authors identifies the dynamics of investment growth over the past decade. It is noted that innovation-related businesses are looking for ways to implement artificial intelligence to optimise processes and gain competitive advantages. A list of business processes and tasks that companies can already improve with the help of AI is compiled and graphically depicted. However, alongside the potential benefits, the article also identifies possible challenges, such as data privacy, ethical considerations and the impact on education. The article concludes with the need for effective state regulation and orientation towards the European Union’s legislation in the field of AI to ensure sustainable development and minimise risks.